22.7k views
3 votes
F(x)+x^2-3x-2x is shifted 4 units left. The result is g(x). What is g(x)

User Marlar
by
5.7k points

1 Answer

2 votes

Answer:

g(x) = x² + 5x + 2

Explanation:

If a function is f(x) = x²

And this function is shifted 4 units left then the rule to be followed is,

g(x) = f(x + 4)

Following the same rule,

For a function f(x) = x² - 3x - 2 when shifted 4 units to the left,

g(x) = f(x + 4)

g(x) = (x + 4)² - 3(x + 4) - 2

= x² + 8x + 16 - 3x - 12 - 2

= x² + 5x + 2

Therefore, g(x) = x² + 5x + 2 will be the transformed function.

User Suchita
by
5.6k points